Misconception Reduction: 4-Tier Diagnostic Test Based on Education for Sustainable Development & Arduino tools - Muhaimin, M Himni; Yaniawati, R Poppy; Sari, Nenden Mutiara; Komala, Elsa; Kastrena, Ervan (PRISMA, 2024)
Misconceptions in mathematics education, particularly in numeracy, are a significant issue that needs to be addressed urgently to improve the quality of education in Indonesia. This research aims to reduce students' misconceptions by developing and implementing a 4-Tier diagnostic test based on Education for Sustainable Development (ESD) supported by Arduino tools in a Problem Based Learning (PBL) model. The method used is mixed methods with a population of 10th-grade high school students and a purposive sampling technique. The research instruments include a 4-Tier diagnostic test and observation sheets. Data were analyzed qualitatively and quantitatively using the concurrent embedded strategy model and the Ploomp research design. The results of the study show that the 4-Tier diagnostic test is effective in mapping students' conceptual understanding and significantly reducing numeracy misconceptions. The implementation of the ESD-based PBL model also proved to enhance students' numeracy skills. This research indicates that integrating diagnostic tests into the curriculum is crucial for improving the quality of learning and students' understanding. The use of Arduino in trigonometry learning increases students' motivation and engagement. Thus, this learning model can be a solution to enhance students' competencies in facing the challenges of globalization and technology in line with UNESCO's Agenda 2030